Principles of curriculum development to improve the quality of learning with Kurikulum Merdeka - Nina Nuraini; Levina Syafin Tejasukmana; Fauzan Yahtadi; Mega Tri Nadya (Universitas Pendidikan Indonesia, 2023)
The curriculum is a reference for education components in carrying out learning. The curriculum must constantly be updated to suit the needs of students from time to time. Curriculum development is essential so learning can follow applicable norms and laws and achieve educational goals, as stated in Law No. 20 of 2003. Until now, the Merdeka curriculum has become a new product of the curriculum development process. This study aims to determine the principles applied to create a curriculum, to know the directions in the Merdeka curriculum, and how the Merdeka Curriculum is developed. This research is descriptive qualitative, where the collection is carried out using the literature study method. Data comes from various literature related to curriculum development. This study describes its findings that the five principles of curriculum development and the characteristics of the independent curriculum are very diverse. The independent curriculum is an innovation that focuses on developing students' competencies to be helpful in society. The Independent Curriculum needs to focus on remote areas of Indonesia to equalize the quality of education throughout the country. Abstrak Kurikulum menjadi acuan bagi para komponen Pendidikan dalam melaksanakan pembelajaran. Kurikulum pun harus selalu diperbarui agar sesuai dengan kebutuhan siswa dari waktu ke waktu. Pengembangan kurikulum penting dilakukan agar pembelajaran dapat berjalan sesuai dengan norma dan hukum yang berlaku serta dapat mencapai cita-cita dari tujuan pendidikan sebagaimana tercantum pada UU No. 20 Tahun 2003. Hingga saat ini, kurikulum Merdeka menjadi produk baru dari proses pengembangan kurikulum. Tujuan penelitian ini adalah mengetahui prinsip-prinsip yang diterapkan untuk membuat kurikulum, mengetahui prinsip-prinsip yang ada di kurikulum Merdeka, bagaimana pengembangan Kurikulum Merdeka. Penelitian ini bersifat deskriptif kualitatif, dimana pengumpulan dilaksanakan dengan metode studi kepustakaan. Data bersumber dari berbagai literatur-literatur yang berkaitan dengan pengembangan kurikulum. Penelitian ini menguraikan temuannya, bahwa lima prinsip pengembangan kurikulum dan karakteristik dari kurikulum merdeka sangat beragam. Kurikulum merdeka menjadi inovasi kurikulum yang berfokus pada pengembangan kompetensi siswa agar dapat bermanfaat di masyarakat. Kurikulum Merdeka perlu untuk berfokus pada daerah pelosok Indonesia guna meratakan kualitas Pendidikan di seluruh negeri. Kata Kunci: Kurikulum merdeka; prinsip pengembangan; prinsip pembelajaran